Pengenalan Alat Musik Tradisional Indonesia bagi Mahasiswa International Summer School 2025 di Universitas Mulawarman, Kalimantan Timur : Introduction to Traditional Musical Instrument Training for International Summer School 2025 Students at Mulawarman University, East Kalimantan - Putra, Doni Septa; Nazhari, Muhammad Aufar Radifan; Susilo, Shirley Frederica; Hutagaol, Angel Syalom Tessalonika; Subagyono, Raden Roro Dirgarini Julia Nurlianti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The introduction to traditional musical instrument training for students of the 2025 International Summer School at Mulawarman University was conducted to showcase Indonesia's cultural wealth through a musical arts approach. This activity aims to provide an understanding of cultural values and practical skills in playing traditional instruments, particularly the sape', gamelan, gong, and gendang, which are used to accompany the East Kalimantan regional song titled "Leleng." The training was organized by the Summer School 2025 Committee in collaboration with the Faculty of Cultural Sciences and was attended by 25 international students from various countries. The series of community service activities consisted of a preparation stage involving planning of materials and equipment, an implementation stage through the introduction of instruments, demonstrations, and hands-on practice assistance, and an evaluation stage to assess participants' level of understanding and satisfaction. Based on the questionnaire results, 90% of participants expressed satisfaction with the implementation of this activity. The results of the activity showed that international students were highly enthusiastic and able to master the basic techniques of playing traditional musical instruments well, even producing simple rhythms in groups. Participants also expressed that this experience not only improved their musical skills but also enriched their cultural knowledge and fostered appreciation for traditional Indonesian art. Overall, the training activity successfully achieved its primary objective: introducing traditional music as part of national identity while serving as an effective cross-cultural learning medium.